Call him Jack : the story of Jackie Robinson, Black freedom fighter - Williams, Yohuru R.; Long, Michael G. (Farrar Straus Giroux, 2022)
This biography of sport's figure Jackie Robinson focuses on his civil rights activism, beginning with how he defended himself from a White rock-throwing neighbor when he was eight years old. Describes how he used his pubic profile as an athlete to draw attention to the injustices perpetrated against African Americans. Highlights the protests he participated in, his public comments, and his debates with leading Civil Rights leaders during the 1960s. The examples from his life show that he was much more than a sports icon, he was a man of principle who couldn't idly sit by and allow racism to persist unchecked.